Monitoring of Cadmium, Lead, and Mercury Levels in Seafood Products: A Ten-Year Analysis - Luisa Garofalo; Marcello Sala; Claudia Focardi; Patrizio Pasqualetti; Daniela Delfino; Francesca D’Onofrio; Barbara Droghei; Francesca Pasquali; Valentina Nicolini; Flavia Silvia Galli; Paola Scaramozzino; Alessandro Ubaldi; et al. (Foods)
The European Food Safety Authority (EFSA) monitors the presence and concentration of contaminants in food to mitigate health risks. EU legislation sets maximum levels of heavy metals in foods, including cadmium (Cd), lead (Pb), and total Hg (THg) in seafood, due to their toxicity. In the framework of official control, between 2014 and 2023, 5854 seafood samples were collected and 4300 analyses for THg, 3338 for Cd, and 2171 for Pb were performed using Inductively Coupled Plasma Mass Spectrometry (ICP-MS) and cold vapor atomic absorption spectrometry (CVAAS). The aim was to assess the proportion of contaminated foods in the dataset, the concentration of contaminants, and the potential health risks associated with their intake. Of the total samples analyzed, 142 (2.43%) were found to be non-compliant (n.c.). Concentrations exceeding the limits for Cd were primarily detected in cephalopods (n = 17), mainly squids. In contrast, Hg levels exceeded the limits in marine fish (n = 118), notably in swordfish (11.30% of n.c. samples among those analyzed for this species), sharks (6.48%), and tuna species (3.11%). Regarding Pb, only a single bivalve sample was found to exceed the maximum limits. A preliminary assessment of weekly exposure to Hg through swordfish consumption raised concerns about the frequent intake of marine top predators, particularly for vulnerable people.